Analisis Perkembangan Karakter Santri Melalui Pembiasaan Shalat Berjamaah di Pondok Pesantren Yapink Pusat Tambun Selatan Bekasi - Ahmad Hidayatullah (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2022)
The background of this research is the problem of juvenile delinquency. This delinquency is formed due to the influence of a less religious environment and the inability of parents to cope with their child's puberty.This study uses a qualitative approach with descriptive analysis method. This research was conducted through field research (field research). The purpose of this study was to determine the process of implementing congregational prayer habituation, to explore the character formation of students through the process of habituation to congregational prayers, and to evaluate the relationship between congregational prayer and the formation of the character of students at the Yapink Islamic Boarding School. The findings of this study are: 1) there is a method of habituation through the routine activities of students who have been programmed, and also through the example of teachers when guiding students, 2) the character that develops through the habit of praying in congregation